The Effect Of Utilization Of Mysql On The Results Of Student Learning In Subject Of Data Basis - Supari Muslim; Didik Triaswira; Erina Rahmadyanti; Soeparno Soeparno; Nita Kusumawati (Universitas Negeri Makassar, 2019)
This study aims to determine: (1) differences in learning activities between students who use MySQL and students who use Ms. Access on subjects in Database Processing with basic competencies in understanding language in class XI of the RPL Department of SMK 2 Surabaya; (2) differences in learning outcomes between students who use MySQL and students using Ms. Access on Database subjects with basic competencies in understanding language in class XI of the RPL Department of SMK 2 Surabaya.The research design used was a